2020
DOI: 10.1016/j.jeem.2020.102384
|View full text |Cite
|
Sign up to set email alerts
|

OPEC, unconventional oil and climate change - On the importance of the order of extraction

Abstract: We show that OPEC's market power contributes to climate change by enabling producers of relatively expensive and dirty oil to start producing before OPEC reserves are depleted. We examine the importance of this extraction sequence effect by calibrating and simulating a cartel-fringe model of the global oil market. While welfare net of climate damage under the cartel-fringe equilibrium can be significantly lower than under a first-best outcome, almost the entire welfare loss is due to the sequence effect of OPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…The production function is Q f = A f X f . 6 Further, in keeping with Figure 1, assume that output is homogenous over productive units, and that the market for inputs is competitive, implying a common output, P , and input prices, P X . Noting that TFPR = P × A f , this implies that dispersion in TFPR is proportional to dispersion in TFPQ, quantity based productivity A f .…”
Section: A the Link Between Misallocation And Productive Inefficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The production function is Q f = A f X f . 6 Further, in keeping with Figure 1, assume that output is homogenous over productive units, and that the market for inputs is competitive, implying a common output, P , and input prices, P X . Noting that TFPR = P × A f , this implies that dispersion in TFPR is proportional to dispersion in TFPQ, quantity based productivity A f .…”
Section: A the Link Between Misallocation And Productive Inefficiencymentioning
confidence: 99%
“…We focus on the standard deviation of TFPR as it seems to be the one most often used. 6 X f can be thought of as an input index for a constant returns to scale technology.…”
Section: A the Link Between Misallocation And Productive Inefficiencymentioning
confidence: 99%
“…85 In addition, some studies confirm that OPEC's oil is cleaner than shale oil, so it is possible will be another pressure card used by OPEC soon with the support of international environmental institutions. 86,87 3-Newly discovered oil and gas reserves in the Middle East, specifically in (Syria and Egypt). 88,89 4-The UK and Australia pursue seriously producing shale oil and shale gas.…”
Section: Eia Scenariomentioning
confidence: 99%
“…Ignoring resource rents, Saboori et al (2016) investigated OPEC from 1977 to 2008 and corroborated the EKC hypothesis in 6 out of 10 investigated OPEC economies. Benchekroun et al (2020) investigated the cartel-fringe model and found that OPEC market power was a source of welfare loss net to climate change. Moreover, rising non-OPEC oil reserves decreased global welfare.…”
Section: Literature Reviewmentioning
confidence: 99%